Collocations of pria, lelaki, and jantan as representations of masculinity in Indonesia - Mika Wulan Dari; Agus Syahrani; Dedy Ari Asfar (Penerbit Universiti Kebangsaan Malaysia, 2024)
Language is one way to understand a society and its culture, including masculine norms. Exploring evolutionary masculinity through language is an intriguing concept to revisit. The research examines words synonymous with "men" in Indonesia and reviews their usage to depict current masculinity in the country. This research applied discourse analysis to corpora sourced from the Leipzig Corpora and CQPWeb. The data were analyzed using semantic preference to find meanings and semantic prosody to find connotations of pria, lelaki, and jantan. The findings reveal differences in the meanings and usage of the pria, lelaki, and jantan words. The difference in meaning is that pria is an adult male, whereas lelaki is a representation of men who are not limited in age, and jantan is interpreted as the genitals of animals or plants and men in the context of masculinity. According to usage, the word pria is frequently used in the public sphere, such as in the context of work and news discourse. Lelaki tends to be used more in the personal sphere, such as family, rather than in public settings. Jantan tends to be used in public discourse. The connotations of pria, lelaki, and jantan is neutral. This study successfully demonstrated the shift in Indonesian masculinity from traditional to new forms, indicating the impact of language studies on the analysis of masculinization in Indonesia.